A Prospective Study Of Functional Outcome Of Fractures Of Short Tubular Bones Of Hand Treated By Mini-Plating (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Metacarpal and phalangeal fractures are always common in adolescents and young active individuals. Aim of the study is to assess a prospective study on functional outcome of closed metacarpal fractures treated with plates and screws. Materials and Methods: Selected patients for study is examined according to protocol, associated injuries noted and clinical examination and lab investigations carried out in order to get fitness for surgery. Consent of the patient will be taken for surgery. Patient will be followed till Union is achieved clinically as well as radiologically. Time required for union, range of motion of surrounding joints and complications occurred before / during / after surgery will be studied in detail. Results: 20 patients were included in this study. 5 patients had multiple metacarpal fractures (25% cases). Right hand was involved in 14 of the patients (70%). 1 out of 20 were female patient (10%). All the 20 patients who underwent open reduction and internal fixation with plate osteosynthesis for unstable metacarpal and phalangeal fractures achieved bone union (100%). In most of the cases bony union was seen between 6-8 weeks, average period being 7.2 weeks (range 6-12 weeks).Functional outcome assessed by ASSH (American Society for Surgery of the Hand) TAF (Total Active Flexion) score was excellent in 16 patients (80%), good in 2 patients (10%), fair in one patient (5%), poor in one patient (5%). The overall results are satisfactory. Conclusion: Plate and screw fixation is a good option for treating closed unstable metacarpal and phalanx fractures, where other modalities of fixation are less effective.